(3cGed GdUfGYI aj GdaQhSjI hGdTLGYIs
(3ChdgG (B:s
(3GdMeO dgd GdPi CPgH YfG GdMRf Ef QHfG dZahQ TchQ bGd GdeDda YaG Gddg Yfg Gfi de CRd HYO Ef hgHg Gddg di ef GdeYQag s
(3BNQgG (B:s
(3aMjfFP JLQ Ydjg aQSc aJWYfg BefG ef QeMg Ke JNQL efg SQjYkG hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QJHg Ydi CQHYjf HGHkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs